A case study of how a leader shaped the culture of an organisation during a post-merger integration - Zozi, Vuyokazi (Rhodes University, Faculty of Commerce, Rhodes Business School, 2020)
This research took the form of a case study of the post-merger integration of a government organisation. The study had four objectives, namely to: (1) describe the cultural value of accountability; (2) analyse how strategic leadership and relational leadership roles were exercised to address post-merger integration challenges; (3) analyse how a leader applied selected primary mechanisms to shape organisational culture; (4) analyse how strategic and relational leadership complemented each other in addressing the challenges of post-merger integration and thereby shaping a culture of accountability; and (5) describe how some of the secondary articulation and reinforcing mechanisms supported the culture that was created through primary mechanisms. The literature reviewed, identified some of the critical challenges that are experienced in a post-merger integration, and highlighted the role of leadership in culture formation. The critical challenges that were identified are as follows: What is the vision and organisational purpose? How does the leader structure the organisation? What kind of culture does the leader need to create? How does the leader maintain trust and keep communication with employees? How does a leader build new core competences and develop human capital? Two leadership approaches were adopted, namely strategic and relational leadership. These two leadership approaches were selected because, based on a review of the literature, they appeared to address these post-integration challenges. The roles associated with strategic leadership that were investigated, were creating a vision and purpose for the organisation, developing core competences and developing human capital. From the perspective of relational leadership, this study was concerned with how a leader communicated through regular formal and informal dialogues to keep employees abreast of things, and how the leader built trust. In reviewing the literature linking leadership and culture, the work of Schein (2010) featured prominently. Schein (2010) referred to primary embedding mechanisms that create culture and secondary articulation and reinforcing mechanisms that reinforce or support the culture being created through the primary mechanisms. This study looked at how that happens, and hence six propositions were crafted from the literature. These propositions are as follows: (1) Formal dialogues between the leader and employees demonstrate what the leader pays attention to, measures and controls, which then clarifies what the employees are accountable for. (2) What the leader pays attention to, measures and controls during regular informal interactions between the leader and employees, contributes to strong mutual relationships between them, which promotes ownership and accountability amongst employees for their actions. (3) A leader who behaves consistently when handling critical incidents and organisational crises, is trusted by employees, who then act responsibly and take full responsibility for their actions, and even their mistakes. (4) A leader creates a vision and sense of purpose for the organisation through what he pays attention to, measures and controls, thereby clarifying for employees what they are required to do. (5) A leader who pays attention to developing the organisational core competence and allocates resources to it, instils confidence in his employees with regards to carrying out their own responsibilities. (6) A leader who develops human capital through the allocation of additional resources, thereby instilling confidence in employees who are willing and able to realise or take up their responsibilities. This research adopted a qualitative approach. Data was collected through conducting interviews and the analysis of relevant documents. A deductive thematic analysis of the data was used for the purpose of identifying, analysing and reporting patterns, or themes within the data collected. The research confirmed these propositions as being relevant to the case study. It also confirmed that strategic and relational leadership as reflected in the propositions have complemented one another in the successful implementation of the post-merger integration, thereby shaping a particular culture. It was concluded that the challenges associated with a post-merger integration could not have been addressed through only one of the leadership approaches. The findings of the study also recognised that an architectural role was also required. That is, in a merger, the structure has to be carefully designed and not taken for granted. It was therefore recognised as a critical leadership role. The study considers the implications of the findings and makes recommendations for managers of this organisation, as well as for other organisations that are engaging in a post-merger integration. It further outlines the limitations, delimitations as well as the contribution that the study has made to the body of knowledge. Some of the recommendations made for further research were to analyse how other primary mechanisms that were not part of the propositions may shape the organisational culture; and to research how architectural leadership roles combine with strategic and relational leadership to address post-merger integration challenges. Lastly, this study has explained how leadership, through various mechanisms, shaped a culture of accountability. Other studies can be done using a similar design with different theories of leadership and other mechanisms that apply to shaping other kinds of cultural values.
Keywords: Corporate culture -- South Africa -- East London; Leadership -- South Africa -- East London; Organizational behavior -- South Africa -- East London; Strategic planning -- South Africa -- East London; Mission statements -- South Africa -- East London; Government accountability -- South Africa -- East London; Government corporations -- South Africa -- East London; Consolidation and merger of corporations -- South Africa -- East London; Consolidation and merger of corporations -- Management; Crisis management -- South Africa -- East London; Core competencies -- South Africa -- East London; Resource allocation -- South Africa -- East London; Personnel management -- South Africa -- East London; Communication in management -- South Africa -- East London; Qualitative research